2021
DOI: 10.1371/journal.pone.0249940
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of rivaroxaban versus warfarin in Taiwanese patients with end-stage renal disease and nonvalvular atrial fibrillation: A real-world nationwide cohort study

Abstract: Background The optimal anticoagulant for end-stage renal disease patients for stroke prophylaxis is unknown. The efficacy and safety of warfarin in this population are debatable. In addition, real-world evidence of direct oral anticoagulants in patients with end-stage renal disease is limited. The aim of this study was to evaluate the clinical outcomes of rivaroxaban compared with warfarin in Taiwanese patients with end-stage renal disease with nonvalvular atrial fibrillation in a real-world setting. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…38,39 Of the 8 remaining retrospective studies, 4 reported efficacy data between DOAC therapy and warfarin, and only 1 found a difference in favor of DOAC therapy. 37,40,41,43 Additionally, Miao et al 46 reported no difference between apixaban and rivaroxaban. Despite a lack of efficacy data, safety outcomes favor DOAC use in patients with AF and CKD-5 or ESKD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…38,39 Of the 8 remaining retrospective studies, 4 reported efficacy data between DOAC therapy and warfarin, and only 1 found a difference in favor of DOAC therapy. 37,40,41,43 Additionally, Miao et al 46 reported no difference between apixaban and rivaroxaban. Despite a lack of efficacy data, safety outcomes favor DOAC use in patients with AF and CKD-5 or ESKD.…”
Section: Discussionmentioning
confidence: 99%
“…The prospective study by De Vriese et al 38 utilized rivaroxaban 10 mg daily, whereas 1 observational study included 155 (90%) patients on 10 or 15 mg daily and another included 560 (70%) patients on the standard dose of 20 mg daily. 37,38,46…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 3 (Ref. [39][40][41][44][45][46][47]) and Table 4 (Ref. [39][40][41][44][45][46][47]) summarize all the large-scale trials mentioned below.…”
Section: Doacs As a Treatment Option For Patients With Af On Hemodial...mentioning
confidence: 99%